Pengawasan (Controling) Dalam Institusi Pendidikan - Iin Meriza (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2018)
The last step in an educational institution management is controlling. controlling includes evaluation through controlling, surveillance, and direction. The ideal controllings are carried out by professionals, who are capable of working through various stages and on proportional goals. Controlling in educational institutions is aimed at the implementation of the overall program, expecting to improve the quality of educational institutions, such as in public schools, pesantren and dayah (Islamic schools) and other educational institutions. Controlling within educational institutions is urgent. Thus, supervisors must understand the steps and strategies of the implementation, can differ supervising and controlling, and know the duties of the school supervisor who serves an important role inthe supervisory task.